Characterization of Collagen Hydrolysate Gel from Mackerel Scad Skin (Decapterus macarellus) - Elisa Herawati; Rizki Sandhi Titisari; Okid Parama Astirin (Jurnal Penelitian Pendidikan IPA, 2023)
The skin of mackerel scad (Decapterus macarellus) is a novel source of marine bioactive collagen hydrolysate that has the potential to improve skin health. Collagen hydrolysate represent the major constituent in cosmetic industry because of its excellent moisturizing properties and multiple health benefits. The purpose of this study is to investigate the application of mackerel collagen hydrolysate (mackerel CH) as a component of cosmetic gel preparations by examining the gel’s physical and chemical properties which include viscosity, spreadability, adhesiveness, gel strength, gel texture, pH, and organoleptic. Evaluation of physicochemical properties is necessary to ensure that the quality and safety of the gel preparation meets the intended specifications. The formulation of the mackerel CH resulted in a gel with higher viscosity and spreadability compared to the standard national guideline (SNI). The gel exhibited favorable adhesiveness and pH levels, indicating its potential to efficiently deliver active substances to the skin without causing any irritation. The results indicated that the gel had a soft consistency in terms of gel strength and texture. Organoleptic assessment described the gel as having a clear, yellowish appearance with a subtle fishy aroma. Future studies should focus on further optimizing the formulation. Additionally, it is recommended to assess the efficacy of this gel in addressing medication-related issues using an animal model